2014
DOI: 10.1186/1465-9921-15-33
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of transplanted mesenchymal stem cells by the lung progenitor niche in rats with chronic obstructive pulmonary disease

Abstract: BackgroundStem cell transplantation is a promising method for the treatment of chronic obstructive pulmonary disease (COPD), and mesenchymal stem cells (MSCs) have clinical potential for lung repair/regeneration. However, the rates of engraftment and differentiation are generally low following MSC therapy for lung injury. In previous studies, we constructed a pulmonary surfactant-associated protein A (SPA) suicide gene system, rAAV-SPA-TK, which induced apoptosis in alveolar epithelial type II (AT II) cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
1
28
1
Order By: Relevance
“…A 0.5 cm long sample of tracheal tissue was excised nearly from the 0.3 to 0.8 com trachea portion lower the stoma, and was fixed in 2.5% glutaraldehyde for 24 h, the specimens were dehydrated and then embedded in paraffin, finally the transverse section of specimens were sliced for HE staining as previously described [19, 20], each tissue section was examined and photopgraphed using an Olympus light microscope (Olympus OX51), Image J software (US National Institutes of Health, Bethesda, MD, USA) was used to calculate the white blood cell counts, we tended to quantify the disarrangement of mucosal epithelium or basement membrane yet no accurate method to resort.…”
Section: Methodsmentioning
confidence: 99%
“…A 0.5 cm long sample of tracheal tissue was excised nearly from the 0.3 to 0.8 com trachea portion lower the stoma, and was fixed in 2.5% glutaraldehyde for 24 h, the specimens were dehydrated and then embedded in paraffin, finally the transverse section of specimens were sliced for HE staining as previously described [19, 20], each tissue section was examined and photopgraphed using an Olympus light microscope (Olympus OX51), Image J software (US National Institutes of Health, Bethesda, MD, USA) was used to calculate the white blood cell counts, we tended to quantify the disarrangement of mucosal epithelium or basement membrane yet no accurate method to resort.…”
Section: Methodsmentioning
confidence: 99%
“…MSCs have been successfully delivered in solution as a therapy for acute lung injury in several models . Despite their success these therapies have failed to produce significant improvement when addressing chronic lung pathologies due to the low retention in the tissue over time . Cell delivery strategies for encapsulating and maintaining the therapeutic efficacy of the dosed cells have been developed from both natural and synthetic materials .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies demonstrated the efficacy of mesenchymal stem cell administration in many lung diseases including acute lung injury,8 bronchopulmonary dysplasia,910 chronic obstructive pulmonary disease,1112 fibrosing pulmonary injury,1314 pulmonary ischemia reperfusion injury,15 radiation induced lung injury,16 sepsis,17 and PAH 7918. Mesenchymal stem cells have an effect on lung inflammation and injury through paracrine interactions rather than direct interaction.…”
Section: Introductionmentioning
confidence: 99%